Peran Good Manufacturing Practice dalam Meningkatkan Mutu Produk dan Daya Saing UD. Elsheha Perspektif Ekonomi Islam - Uswatun Hasanah; Siti Habibatur Rahma (Institut Agama Islam Sunan Giri Ponorogo, 2026)
The implementation of Good Manufacturing Practice (GMP) is an important strategy to improve product quality and strengthen the competitiveness of food Micro, Small, and Medium Enterprises (MSMEs). However, studies on GMP implementation through an in-depth qualitative approach at the MSME level, particularly in relation to improving product quality and business competitiveness from an Islamic economic perspective, are still relatively limited. This study aims to analyze the implementation of GMP at UD. Elsheha, evaluate its compliance with the principles of Good Processed Food Production Practices (CPPOB), and examine its role in improving product quality and business competitiveness. The study used a qualitative approach with a case study design through observation, semi-structured interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing, while data validity was tested using source triangulation. The results of the study indicate that UD. Elsheha has implemented most of the GMP principles, including raw material control, sanitation, environmental cleanliness, process control, storage, and product distribution. However, improvements are still needed in the consistency of the use of personal protective equipment, documentation systems, the development of standard operating procedures, and product traceability. The implementation of GMP contributes to improved product quality, production process consistency, consumer trust, and business competitiveness. From an Islamic economic perspective, GMP implementation reflects the principles of halal, thayyiban, amanah, and ihsan, demonstrating producer responsibility in producing safe, high-quality, and sustainable products.